Alternate Dough Preparation Protocol for Extensigraph Test of Dough Strength. Issue 2 (29th August 2016) - Suchy, Jerry; Dupuis, Brigitte; Sakamoto, Jun; Fu, Bin Xiao
Abstract : The extensigraph is an internationally accepted method for measurement of physical properties of dough subjected to mechanical handling and resting. Standard extensigraph methods (AACC International Approved Method 54‐10.01, ISO 5530‐2) use the farinograph for the preparation of dough in the presence of 2% salt at reduced water absorption (farinograph absorption minus 2–3%). However, the dough so prepared is usually underdeveloped and drier than typically seen in common baking processes. In addition, the standard extensigraph test is time consuming and requires a large sample size. In this study, an alternate dough preparation protocol is proposed, consisting of a Swanson‐type pin mixer at reduced salt (1%) and elevated water absorption (farinograph absorption plus 4%). With the alternate method, dough is fully developed and similar to bread dough in physical properties.AACCI Approved Method 54‐10.01 is followed for dough rounding, molding, resting, and stretching by using the Brabender Extensograph‐E instrument. Strong correlations for resistance to extension ( r = 0.90) and area ( r = 0.92) were found between the modified and standard dough preparation methods. This protocol requires much less flour sample and significantly increases sample throughput.